Khartoum Stock Exchange: The Reality and the Requirements of Improvement Comparative study of the stock markets of some Arab countries - Mohamed, Abdelrahman Musa Ali (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify the reality of Khartoum Stock Exchange (KSE) compared to stock markets in some Arab countries, by evaluating and comparing the factors of measuring the efficiency of the market. The study followed two methodologies; the first is a descriptive methodology by reviewing previous studies, discussing the experts’ opinions and the statistics provided by the Arab Monetary Fund on the performance of (KSE) and summarizing it scientifically. The second approach is the comparative approach between the financial market of Khartoum, Saudi Arabia and Egypt by conduct statistical tests to test the convergence of the indicators of the efficiency of the (KSE) with the indicators of measuring the efficiency of the Arab stock markets. The study reached a number of results which are expected to have a negative impact on the possibility of improving the future efficiency of the market if they are not remedied. These include the small number of companies of (KSE), the small size of (KSE) to the Sudanese economy, poor indicators of measuring liquidity of the market, weak correlation between indicators measuring the efficiency of (KSE) and economic growth, no effect of economic growth to enhance and increase investments in the market.